PERAN APARAT PENGAWAS INTERN PEMERINTAH (APIP) DALAM PENYELENGGARAAN PEMERINTAHAN DAERAH DI KABUPATEN BULUNGAN - Elieser Yohanes (Jurnal Paradigma (JP), 2018)
This research is aimed to describe and analyze the role of Government Internal Auditor (APIP) In the local government management at Bulungan District. This study used a descriptive qualitative approach, data collection techniques is participant observation, interview and documentation, which is then analyzed using component of data analysis:interactive model. The results showed that (1) the role of Government Internal Auditor (APIP) in the local government management at Bulungan District realized through implementation of comprehensive inspection to government affairs management by regional government device at Bulungan District, which includes the inspection of the institutional and staffing aspects; inspection of the financial aspects; and inspection of local government asset management aspects. (2) Apply the comprehensive inspection concept in implementation of regular inspections cause The role of Government Internal Auditor (APIP) in the local government management at Bulungan District ineffective.Keywords: Government Internal Auditor, Regular Inspection, Comprehensive Inspection